2007
DOI: 10.5102/prismas.v3i1.214
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversidade E Conhecimentos Tradicionais

Abstract: RESUMOOs conhecimentos tradicionais são informações de comunidades indígenas ou de comunidades locais que apresentam valor real ou potencial associado ao patrimônio genético. Contudo, nem sempre o conhecimento tradicional é reconhecido e protegido da forma que deveria ser. Este artigo tem como objetivo apontar os principais instrumentos legais utilizados, internacionalmente e nacionalmente, na proteção da biodiversidade e dos conhecimentos tradicionais relacionados a ela. Assim, serão analisados, entre outros,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
2
0
4
Order By: Relevance
“…Ethnobotany is the science that ingrates the relationships between men, in their varied cultural forms of association, and plant diversity. Used either in the context of scientific production and business activities, studies approaching this perspective guide the actions of bioprospection, a field that explores biological diversity to seek genetic and biochemical resources of commercial value by acknowledging their use from the traditional knowledge of the community and/or individual user (Pereira, 2008) to popularize it aim at an economic appropriation (Andrade, 2006). Pereira (2008) reported that bioprospection can use the knowledge from traditional communities to survey the associated biological, genetic or even methodologic resources to provide humankind with many benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnobotany is the science that ingrates the relationships between men, in their varied cultural forms of association, and plant diversity. Used either in the context of scientific production and business activities, studies approaching this perspective guide the actions of bioprospection, a field that explores biological diversity to seek genetic and biochemical resources of commercial value by acknowledging their use from the traditional knowledge of the community and/or individual user (Pereira, 2008) to popularize it aim at an economic appropriation (Andrade, 2006). Pereira (2008) reported that bioprospection can use the knowledge from traditional communities to survey the associated biological, genetic or even methodologic resources to provide humankind with many benefits.…”
Section: Introductionmentioning
confidence: 99%
“…However, as pointed out by Andrade (2006), the local communities studied are not always acknowledged or appreciated equally by scientists or companies that carry out bioprospection investigations. Because of this, Silva et al (2015) alerted that the loss of traditional knowledge leads to disregard the conservation of plant resources, or even generating loss of biological diversity.…”
Section: Introductionmentioning
confidence: 99%
“…O conhecimento tradicional é um patrimônio comum do grupo social, possui caráter difuso, pois não pertence a apenas um indivíduo, mas sim a toda a comunidade. O termo conhecimento tradicional refere-se a todas as informações, práticas, individuais ou coletivas, relacionadas aos recursos genéticos, desenvolvidos e utilizados por essas comunidades(Goater, 2007;Andrade, 2006).…”
unclassified
“…• Estágio 4 -Autorização da Vigilância Sanitária: i) o órgão sanitário regulador aprova a nova droga; ii) introdução da nova droga ao mercado, que requer pesquisa de mercado, análise de lucros, planejamento de produção, marketing e distribuição (ANDRADE, 2006). Após aprovação da nova droga, em alguns casos, nos EUA, o FDA exige da empresa a realização de estudos adicionais conhecidos como "pós-comercialização", que avaliam a segurança no longo prazo ou fornecem mais dados sobre os efeitos peculiares do medicamento em grupos específicos de doentes, como crianças ou idosos.…”
Section: A Bioprospecção E a Indústria Farmacêuticaunclassified
“…No entanto, além dos tipos de contratos existentes para recursos genéticos, há diferenças evidentes entre contrato de acesso e contrato de pesquisa, além das distinções. Há três formas de contratos sobre recursos genéticos: o contrato de prospecção in situ, o contrato de transferência de um material já coletado e o contrato de pesquisa (ANDRADE, 2006).…”
Section: Contratos Da Bioprospecção Como Forma De Diminuir As Incertezasunclassified